The impact of the organization’s future vision on enhancing social value (Analytical research at the Ministry of Labor and Social Affairs) - et. al., Ass. Prof. Dr. Ali Mawat Al-Sudani, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to determine the nature of the future vision relationship and its role in enhancing the social value of the organization on which the research was conducted (Ministry of Labor and Social Affairs), as the future vision represents the compass that directs the organization’s activities towards achieving its goals, including creating and maintaining social value in the community in which the organization is located. The statement of problem revolved around exploring the nature of the relationship between the future vision and the creation of social value, and for this purpose the researcher adopted the descriptive analytical approach, and the Ministry of Labor and Social Affairs was chosen as a research community with a number of (850) individuals, while the research sample was deliberately chosen from the research community,represented by the general managers and their assistants, department managers and their assistants, division officials and their assistants, with a number (265), and the questionnaire was used as a research tool with a recovery rate of (98.1%). And the research came out with a set of recommendations, the most important of which is the necessity of owning the organization The respondents have a clear future vision, with the fact that they must be characterized as expressing the organizational goals in a clear way and what they aspire to, with the ability to be applied in a practical way in addition to the need to be convincing to its members, as well as working to strengthen and diversify the social activities of the organization as it is necessary to achieve its social value.